(untitled) (Kathmandu University Medical Journal, 2020)
Background The global health community has emphasized the importance of reporting epidemiological data by age and sex groups in the COVID-19 pandemic. However, age and sex disaggregated data of COVID-19 cases and deaths are rarely reported. Such data are very crucial for public to make truly informed choices about their own diseases risk and also for governments for public policy response. Objective To assess age and gender difference among COVID-19 cases and deaths in Nepal. Method This is a retrospective study which uses public data on COVID-19 cases and deaths released by Ministry of Health and Population, Government of Nepal from January to November, 2020. The data analysis was carried out using SPPS software version 26. Result Nepal reported 233,452 confirmed cases and 1,566 deaths of COVID-19 from 23 January 2020 to 30 November 2020. We found statistically significant differences on COVID-19 cases by age and gender in Nepal with higher number of cases among males of economically active age groups (20-60 years). Similarly, we found significant difference in COVID-19 mortality with more death occurred among male group compared to female group and with highest number of deaths among the people of above 60 years. Furthermore, we found differences in cases and deaths among provinces. Conclusion The age and gender differences in COVID cases and deaths in Nepal indicates needs of considering age and sex groups seriously while planning for testing, case management and vaccination against COVID-19 infections in Nepal.